Trend and future of diesel engine: Development of high efficiency and low emission low temperature combustion diesel engine - Ho R.J.; Yusoff M.Z.; Palanisamy K. (Institute of Physics Publishing, 2023)
Stringent emission policy has put automotive research & development on developing high efficiency and low pollutant power train. Conventional direct injection diesel engine with diffused flame has reached its limitation and has driven R&D to explore other field of combustion. Low temperature combustion (LTC) and homogeneous charge combustion ignition has been proven to be effective methods in decreasing combustion pollutant emission. Nitrogen Oxide (NOx) and Particulate Matter (PM) formation from combustion can be greatly suppressed. A review on each of method is covered to identify the condition and processes that result in these reductions. The critical parameters that allow such combustion to take place will be highlighted and serves as emphasis to the direction of developing future diesel engine system. This paper is written to explore potential of present numerical and experimental methods in optimizing diesel engine design through adoption of the new combustion technology. Published under licence by IOP Publishing Ltd.